Sosialisasi Pada Siswa SMK N 7 Surakarta Untuk Meningkatkan Rasa Percaya Diri - Agatha Cahya Kusuma Wardani; Tiara Fadhilah Hasna Fadholi; Toti Cahya Berlian; Musyafiroh Wahiddatul Sholihah (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
Mental health problems are of particular concern in the community. Health problems are not only seen from that, but also from how a person can explore himself and in his interactions with the surrounding environment. One of the causes of mental health problems that often occurs is a problem of lack of self-confidence or a lack of dissatisfaction and self-confidence. Insecure is a feeling of insecurity, or fear caused by dissatisfaction and lack of confidence in one's own capacities. Vocational High School students are a period when a person enters adolescence so that, Adolescence is a period in life to grow in search of identity and self-identity on the way to adulthood. Self-confidence can simply be interpreted as a belief in one's own abilities or strengths, which can be maximized to achieve expectations and goals. The method in this service is carried out by means of lectures which are attended by 1 class XI PS from SMK Negeri 7 Surakarta. The result of this service that is obtained is in the form of an informant's understanding related to methods or management when individuals experience insecurity.